Rational CCL5 mutagenesis integration in a lactobacilli platform generates extremely potent HIV-1 blockers - Lanzafame, Massimiliano; Grampa, Valentina; Vangelista, Luca (Nature Research, 2018)
Efforts to improve existing anti-HIV-1 therapies or develop preventatives have identified CCR5 as an important target and CCL5 as an ideal scaffold to sculpt potent HIV-1 entry inhibitors. We created novel human CCL5 variants that exhibit exceptional anti-HIV-1 features using recombinant lactobacilli (exploited for live microbicide development) as a screening platform. Protein design, expression and anti-HIV-1 activity flowed in iterative cycles, with a stepwise integration of successful mutations and refinement of an initial CCL5 mutant battery towards the generation of two ultimate CCL5 derivatives, a CCR5 agonist and a CCR5 antagonist with similar anti-HIV-1 potency. The CCR5 antagonist was tested in human macrophages and against primary R5 HIV-1 strains, exhibiting cross-clade low picomolar IC50 activity. Moreover, its successful combination with several HIV-1 inhibitors provided the ground for conceiving therapeutic and preventative anti-HIV-1 cocktails. Beyond HIV-1 infection, these CCL5 derivatives may now be tested against several inflammation-related pathologies where the CCL5:CCR5 axis plays a relevant role.
https://www.nature.com/articles/s41598-018-20300-9
Keywords: CCL5; mutagenes; HIV-1 blockers; Research Subject Categories::MEDICINE; lactobacilli